Randomized control trials and qualitative impacts: What do they tell us about the immediate and long-term assessments of productive safety nets for women in extreme poverty in West Bengal? - Naila Kabeer; Sanchari Datta (London School of Economics and Political Science (LSE), Department of International Development, 2020)
This paper is intended to show the strengths, weaknesses and potential complementarities of different methodological approaches to impact assessment. It reports on the approach and findings reported by a randomized control trial of BRAC's Targeting the Ultra-Poor programme, directed towards women in extreme poverty, that was piloted in a district of West Bengal. It then reports on the approach and findings reported by a qualitative impact assessment of different pilot of the same programme that was carried out by the authors in a neighbouring district of West Bengal around the same time. Both the RCT and the qualitative study revisited their respective pilots a few years later, allowing them to provide some longer-term insights into what the pilots had achieved. The study discusses what the two methodological approaches were, and were not, able to do. It concludes that integrated approaches that use quantitative methods in combination with a variety of qualitative approaches are far more useful for measuring and understanding impacts than reliance on a single method. It also reflects on what might be the key lessons to take away from these studies with regard with the short and longer term achievements of the Targeting the Ultra-Poor approach to the design of productive safety nets for women in extreme poverty.
Keywords: 330; Armutsbekämpfung; Weibliche Arbeitskräfte; Produktivitätsentwicklung; West Bengal